Serum microRNA-126 expression as a biomarker of diabetic retinopathy (Universa Medicina, 2023)
BackgroundDiabetic retinopathy (DR) is a microvascular complication of diabetes mellitus (DM). Diabetic retinopathy causes permanent blindness in the productive age group and has a multifactorial pathogenesis. MicroRNA-126 (miRNA-126) regulates the expression of the vascular endothelial growth factor (VEGF) gene at the post-transcriptional level, VEGF being an important angiogenic protein regulating inflammation in DR development. This study aimed to determine serum miRNA-126 expression as a biomarker in DM patients with DR.MethodsThis was a cross-sectional study involving 4 healthy persons and 21 type 2 DM patients. Subjects consisted of 4 groups: i) healthy controls, ii) DM patients without diabetic retinopathy (NDR), iii) DM patients with non-proliferative DR (NPDR) and iv) DM patients with proliferative DR (PDR). Venous blood was collected from subjects for miRNA-126 examination by real-time polymerase chain reaction (PCR). MiRNA-126 in each group was analyzed using the One Way Anova test and p